Introduction to Dalton Transactions themed issue – New Talent: Europe (2022). Issue 28 (11th July 2022) - Morris, Russell E.; Karppinen, Maarit; Ceroni, Paola
Abstract : Russell E. Morris, Maarit Karppinen and Paola Ceroni introduce the Dalton Transactions themed issue "New Talent: Europe 2022".